(untitled) - Stratten, Scott (Hoboken, New Jersey, 2014)
UnSelling is about everything but the sell. We put all of our focus on the individual purchase transaction, while putting the rest of our business actions second. We've become blind to customer service, support, branding, experiences and even product quality. Sixty percent of a purchasing decision is made before a customer even contacts you. We have funnel vision, and it needs to stop. Unselling is about the big picture: creating repeat customers, not one-time buyers. Create loyal clients that refer others, not faceless numbers. Becoming the go-to company for something, before they even need you. You don't need social media, but you can be connecting with your clients socially. Your video doesn't have to be viral in front of a million people, just contagious in front of your specific market. Content, connection, engagement. It's time to separate from the pack of noise. It's time to UnSell .
Keywords: Kênh tiếp thị,Marketing channels